Synergistic encapsulation of the anti-HIV agent efavirenz within mixed poloxamine/poloxamer polymeric micelles - Chiappetta, Diego Andrés (2011)
This study investigated the synergistic performance of mixed polymeric micelles made of linear and branched poly(ethylene oxide)-poly(propylene oxide) for the more effective encapsulation of the anti-HIV drug efavirenz. The co-micellization process of 10% binary systems combining different weight ratios of a highly hydrophilic poloxamer (Pluronic F127) and a more hydrophobic poloxamine counterpart (Tetronic T304 and T904) was investigated by means of dynamic light scattering, cloud point and electronic spin resonance experiments. Then, the synergistic solubilization capacity of the micelles was shown. Findings revealed a sharp solubility increase from 4 μg/ml up to more than 33 mg/ml, representing a 8430-fold increase. Moreover, the drug-loaded mixed micelles displayed increased physical stability over time in comparison with pure poloxamine ones. Overall findings confirmed the enormous versatility of the poloxamer/poloxamine systems as Trojan nanocarriers for drug encapsulation and release by the oral route and they entail a relevant enhancement of the previous art towards a more compliant pediatric HIV pharmacotherapy. From the Clinical Editor: In this study, the authors demonstrate the versatility of poloxamer/poloxamine systems as Trojan nanocarriers for anti-HIV drug encapsulation and release by the oral route. A highly relevant stability and solubility enhancement is shown, which may ultimately lead to more compliant anti-HIV pharmacotherapy.